2019
DOI: 10.1016/j.jchemneu.2019.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Axonal degeneration and demyelination following traumatic spinal cord injury: A systematic review and meta-analysis

Abstract: The pathophysiology of SCI are poorly understood.  Axonal and myelin sheath properties was changed as time elapsed from the injury. The pathophysiology of axons and myelin sheath differ in various phases of SCI.  These changes are affected by multiple factors related to the injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 76 publications
0
26
0
Order By: Relevance
“…Damage to the spinal cord often results in the degeneration of corticospinal axons (Hill et al, 2001;Hassannejad et al, 2019) which can alter characteristics of physiological responses of the corticospinal tract (Ellaway et al, 2007;Oudega and Perez, 2012). For instance, it has been demonstrated that in people with SCI amplitudes of MEPs are reduced, latencies are prolonged, and motor thresholds are increased compared to uninjured controls (Davey et al, 1998;Ellaway et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Damage to the spinal cord often results in the degeneration of corticospinal axons (Hill et al, 2001;Hassannejad et al, 2019) which can alter characteristics of physiological responses of the corticospinal tract (Ellaway et al, 2007;Oudega and Perez, 2012). For instance, it has been demonstrated that in people with SCI amplitudes of MEPs are reduced, latencies are prolonged, and motor thresholds are increased compared to uninjured controls (Davey et al, 1998;Ellaway et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…After demyelination, myelinated sheath reappears around the axons gradually in the chronic phase of injury. However, thickness and length of this regenerated myelin are smaller than in intact axons, leading to a decrease in conduction velocity and an increase in the reflex latency [17][18][19].…”
Section: Reflex Latencies In Both Groupsmentioning
confidence: 97%
“…When the spinal cord is injured, the primary injury caused by the initial traumatic event are followed by the secondary injuries created by a series of biological and functional changes including activation of autophagy in the dorsal root ganglia, demyelination, trans-synaptic degeneration [17][18][19][20]. Demyelination following SCI is a result of rapid death of oligodendrocytes which are vulnerable to damage.…”
Section: Reflex Latencies In Both Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of this technique is a common method in animal meta-analysis studies. [22][23][24][25] Outcome First, we aimed to evaluate the effect of MSCs-CM on pulmonary fibrosis score, lung collagen deposition, collagen subtypes expression, TGF-β1 expression and other profibrotic chemokines. Since meta-analysis should be performed when the outcome has been reported in at least two studies, we had to assess pulmonary fibrosis score, lung collagen deposition, type I collagen, type III collagen, TGF-β1 expression and interleukin 6 (IL-6) expression.…”
Section: Data Gathering and Synthesismentioning
confidence: 99%